I Ternak and Innovation in the Making of Animal Farmers Data Group Applications for North Sumatra Province - Adi Suhendra (International Journal of Regional Innovation, 2021)
Lack of animal food availability to meet the needs of food security in Indonesia causes the government to import to various countries so that food stock needs are safe, this indicates that our country still depends on other countries to meet the needs of animal food, the lack of adequate empowerment of cattle farmers, especially in West Sumatra made the writer to be the background for this research. To solve the problem of the lack of empowerment of cattle farmers, the government has made innovations, by making the I application of cattle and the application of data grouping . The method used in this research is descriptive by conducting interviews with several sources with qualitative analysis, the results obtained that the application provides benefits to cattle farmers, this can be seen by increasing investors and increasing coordination between cattle farmers.